2022
DOI: 10.1111/jam.15355
|View full text |Cite
|
Sign up to set email alerts
|

Quorum quenching and anti-biofilm activities of halotolerant Bacillus strains isolated in different environments in Algeria

Abstract: Aims The current study aimed to screen Bacillus strains with wide‐spectrum quorum quenching (QQ) activity against N‐acyl‐l‐homoserine lactones (AHLs), helpful in controlling virulence traits in Gram‐negatives, including biofilm formation and also with anti‐biofilm activity against Gram‐positives. Methods and Results A total of 94 halotolerant strains of Bacillus isolated from soil and salt‐lake sediment samples in Algeria were examined for the presence of QQ activity against AHLs, the presence of the aiiA gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…The PCR results confirmed the absence of the aiiA gene in B. velezensis D-18, which aligns with findings in other Bacillus spp. [29,32]. However, PCR results confirmed the presence of the homologous lactonase gene ytnP (584 bp) in B. velezensis D-18, suggesting an alternative mechanism for QQ activity in accordance with previous studies that identified homologous lactonase-producing genes in Bacillus species [25,29,32].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The PCR results confirmed the absence of the aiiA gene in B. velezensis D-18, which aligns with findings in other Bacillus spp. [29,32]. However, PCR results confirmed the presence of the homologous lactonase gene ytnP (584 bp) in B. velezensis D-18, suggesting an alternative mechanism for QQ activity in accordance with previous studies that identified homologous lactonase-producing genes in Bacillus species [25,29,32].…”
Section: Discussionsupporting
confidence: 89%
“…subtilis CECT39, and B. cereus CECT148 was extracted and purified using the GeneJET genomic DNA isolation kit (Thermo Scientific, Waltham, MA, USA) to ascertain the presence of lactonaseproducing genes within the genome of B. velezensis D-18. The experiment utilized specific primers for aiiA (Fw 5 ′ -CGGAATTCATGACAGTAAAGAAGCTTTA-3 ′ ; Rv 5 ′ -CGCTCGAGTATATATTCAGGGAACACTT-3 ′ ) [31,32] and ytnP (Fw 5 ′ -ATCGGATAA-TCATCGTAAGC-3 ′ ; Rv 5 ′ -ATTGAACTAAGAACAGACCC-3 ′ ) [29], which are considered lactonase producer genes. B. cereus CECT148 served as the aiiA control, while B. subtilis subsp.…”
Section: Pcr Genetic Analysismentioning
confidence: 99%
See 2 more Smart Citations